Preventing Polio Post-eradication: Revertant Proportion Patterns of OPV Serotypes. (4th October 2017) - Altamirano, Jonathan; Sarnquist, Clea; Garcia-Garcia, Lourdes; Reyes, Leticia Ferreyra; Montero-Campos, Rogelio; Cruz-Hervert, Luis Pablo; Holubar, Marisa; Talib, Aisha; Purington, Natasha; Halpern, Meira; Behl, Rasika; Ferreira, Elizabeth; et al.
Abstract: Background: As wild poliovirus is eradicated and countries switch from oral polio vaccine (OPV) to inactivated polio vaccine (IPV), preventing circulating vaccine-derived poliovirus is a top priority. However, the stability of Sabin vaccine serotypes remains a concern in undervaccinated communities. We sought to measure the canonical point mutation rates associated with OPV serotype neuroreversion and vaccine-associated paralytic polio (VAPP) as possible markers of serotype fitness. Mexico provides a natural environment to study these patterns as it provides routine IPV immunization and bi-annual OPV campaigns. Methods: We enrolled 450 households with children eligible for OPV before the February 2015 national immunization week from three communities near Orizaba, Mexico. In each community, a different proportion of eligible children received OPV (10, 30, and 70%). Transmission was measured by PCR detection of OPV in samples collected serially from vaccinated children, their households, and other families in the community. Positive samples were reanalyzed to quantify revertant proportion (RP), the percent of OPV VAPP mutants found in positive samples. Results: 15, 109 samples were collected and analyzed from 1, 828 participants. 554 (3.7%) were OPV positive, and 194 have been reanalyzed for RP to date. The majority of OPV 1 positive samples showed <25% revertance as late as 71 days post-vaccination (Figure 1). By contrast, OPV 2 and OPV 3 positive samples quickly revert to VAPP OPV. The majority of OPV 2 positive samples were >75% revertant by Day 7 (Figure 2), while the majority of OPV 3 positive samples were >75% revertant by Day 4 (Figure 3). Conclusion: OPV 1 appears to be more stable than OPV 2 and OPV 3, remaining <25% revertant 71 days post-vaccination. OPV 2 reverts quickly, with most samples reverting to VAPP by Day 7, while OPV 3 reverts the fastest, with most samples reverting to VAPP by Day 4. Understanding the stability of OPV and VAPP mutants may shed some light on the ability of OPV serotypes to persist in community circulation. Analyses regarding potential covariates for VAPP and RP are currently underway. Disclosures: All authors: No reported disclosures.